The Effect of Utilitarian and Hedonic Values on Consumption Behavior in Online Purchase of Fashion Sneakers among Generation Z - Yusa, Viola De; MS, Mahrinasari; Bangsawan, Satria (International Journal of Business, Economics & Financial Studies, 2023)
Today, the contemporary world offers a wide range of fashion products such as apparel, accessories, luggage, and shoes in Indonesia. All shoe firms try to make excellent items, which becomes a huge draw for Generation Z called internet generation. This study investigates the effect of utilitarian and hedonic values on Generation Z purchase of fashion sneakers. It was a quantitative review that used the causality technique and a total of 200 people who wore sneakers were selected as the participants. Data were then analyzed using SmartPLS and a measurement model technique (outer model). The results showed that utilitarian and hedonic values significantly affect Generation Z online purchasing of sneakers. This indicates that the two variables cause people to behave consumptively, starting with viewing artists or acquaintances, affiliations and associations, as well as others.